PEMBINAAN MANAJEMEN EKONOMI SYARIAH ANGGOTA KOPERASI WANITA SYARIAH AS SALAM BULUSARI TULUNGAGUNG - Agus Eko Sujianto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Institutionally, the Sharia Cooperatives for Women (Koperasi Wanita Syariah, Ind.) in East Java were established top down based on the Minister of Home Affairs Regulation and the East Java Governor's Decree. This community service research was conducted at the Koperasi Wanita Syariah “As-Salam” of Bulusari, Tulungagung owing to the fact it is categorized as an active institution in Tulungagung. From a thorough observation, the institution has been relatively applying sharia principles in its operation, for example, by conducting wadi'ah deposit service. However, it has not applied the management of zakat yet as proofed by the fact that, in its 2017 and 2018 financial years, it did not execute zakat as the fourth pillar of Islam. The coaching of sharia management to the members of this institution is meant to become a learning medium in implementing sharia economy as one of important economic components to realize a Muslim state which spreads the blessing for all (raḥmatan li al-ālamīn).